Optimal regularity for the thin obstacle problem with CO,α coefficients - Rüland, Angkana; Shi, Wenhui (Arxiv, 2016)
In this article we study solutions to the (interior) thin obstacle problem under low regularity assumptions on the coefficients, the obstacle and the underlying manifold. Combining the linearization method of Andersson \cite{An16} and the epiperimetric inequality from \cite{FS16}, \cite{GPSVG15}, we prove the optimal $C^{1,\min\{α,1/2\}}$ regularity of solutions in the presence of $C^{0,α}$ coefficients $a^{ij}$ and $C^{1,α}$ obstacles $φ$. Moreover we investigate the regularity of the regular free boundary and show that it has the structure of a $C^{1,γ}$ manifold for some $γ \in (0,1)$.
Im Titel sind "0" und "α" hochgestellt
Gesehen am 26.05.2021